KALTA POYALI BUG‘DOY SELEKSIYASI UCHUN DASTLABKI MATERIAL. (AGROINNOVATSIYА, 2024)
The condusion was made on the opportunity of imposing mild wheat varieties at the expense of donor's undersized Valuable selection material was created on this basis concerning selection programmer for irrigated conditions